Application of TOEH Framework to Analyze Readiness for Adoption of Information Technology in Institutions in Central Java - Agung Christianto , Paminto; Susanto, Eko Budi (IndoCompt Publisher, 2025)
Digital transformation in the public sector requires organizational readiness to adopt information technology (IT) effectively. This study aims to analyze the factors that influence IT adoption readiness in agencies in Central Java using the TOEH (Technology, Organization, Environment, Human Resources) framework approach. Data collection was conducted through a survey of 102 respondents representing employees of related agencies, with a purposive sampling technique and a Likert scale questionnaire instrument. The results of the validity test showed that all instrument items were valid, and the reliability test showed that the Technology variable (α = 0.899) was the most reliable compared to Organization (0.659), HR (0.587), and Environment (0.485). The findings showed that aspects of system security, managerial support, government policy, and HR competence were key factors in IT adoption readiness. This study emphasizes the importance of synergy between internal and external elements of the organization in supporting public sector digital transformation.